Human mnesic performance in a survival scenario: the application of the adaptive memory concept in ethnobiology - da Silva, Risoneide Henriques; Muniz de Medeiros, Patrícia; Soares Ferreira Júnior, Washington; Paulino Albuquerque, Ulysses (Ethnobiology and Conservation, 2017)
Evolutionary psychologists suggest that the human brain has evolved to retain information of greater adaptive value in a differentiated manner, being this information relevant for survival. These premises are part of a research field defined as adaptive memory. This article reviews the main studies related to adaptive memory, indicating its recent findings, as well as discussing the possible applications of the theme to studies in evolutionary ethnobiology.